Побудова алгоритму автоматичної індексації повнотекстових документів за ключовими словами - Каніщева, Ольга Валеріївна; Ляхвацкая, О. М. (Харківський національний університет радіоелектроніки, 2011)
The given work is devoted working out information and the lingware for the automated indexing by keywords of the text-through document which is convenient and more useful in sphere of analysis of the text for the user. In this article it is considered the analysis of a subject domain and statement of the task for automatic indexation of the document on keywords is considered, have analysed existing methods of automatic indexation of text-through documents. The review of modern industrial systems which realise automatic indexation by keywords is made. The algorithm of indexation text-through is shown the document
Keywords: інформаційний пошук; бінарне індексування; морфологічне індексування; програмні системи; Галактика-ZOOM; УІС Росія; Russian Context Optimizer (RCO)